Aplikasi Menu Restoran Sushi Jepang Menggunakan Augmented Reality (AR) - Yesmaya, Violitta; Devin, Devin; Roesli, Aldo Biondy; Primaguna, Radik (Jurnal Telematika, 2019)
The development of technology is now increasingly rapid. This can be proven from the many applications that make it easier for users to carry out their daily activities. Many restaurants offer food menus, but not all food menus are visualized on the menu book. This makes the customers always ask back to the staff about the menus from the restaurant. From these problems, research is made that can facilitate users in ordering food displayed in 3D, so that the appearance of the food menu is more clear and attractive to users. The method used in this study is the waterfall method where the application development is carried out systematically. The waterfall method has several steps that must be followed: requirements analysis and definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. The results of the study are "Sushiapp" an application that applies augmented reality technology in visualizing several types of sushi. The research was developed on the Android platform, so users can see a more visual menu display and make it easier for users to order food according to the 3D display.Perkembangan teknologi sekarang sudah semakin pesat, hal ini dapat dibuktikan dari banyaknya applikasi yang memudahkan pengguna dalam melakukan aktifitasnya sehari-hari. Banyaknya restoran yang menawarkan menu makanan, namun tidak semua menu makanan tervisualisasikan pada buku menu. Hal ini yang membuat para pelanggan selalu menanyakan kembali kepada pihak restoran menu terfavorit dari restauran tersebut. Dari permasalahan tersebut dibuatlah penelitian yang dapat memudahkan pengguna dalam melakukan pemesanan makanan yang ditampilkan dalam bentuk 3D sehingga tampilan menu makanan lebih jelas dan menarik bagi pengguna. Metode yang digunakan dalam penelitian ini adalah metode waterfall yang dimana pengembangan aplikasi dilakukan secara sistematik. Dari metode waterfall ini memiliki beberapa tahapan yang harus dijalani: requirement analysis and definition, system and software design, implementation and unit testing, integration and system testing, dan operation and maintenance. Hasil dari penelitian adalah “Sushiapp” sebuah aplikasi yang menerapkan teknologi augmented reality dalam memvisualisasikan beberapa macam jenis sushi. Penelitian dikembangkan pada platform Android, sehingga pengguna dapat melihat tampilan menu yang lebih visual dan memudahkan pengguna dalam memesan makanan sesuai dengan tampilan 3D.